국내 미혼모의 양육스트레스 관련 연구 분석 - 방경숙(Kyung-Sook Bang); 김성재(Sungjae Kim); 정예슬(Yeseul Jeong); 송민경(Min Kyung Song); 이금희(Gumhee Lee); 임지희(Jihee Lim) (Seuteureseu yeon-gu (Online), 2019)
본 연구는 국내 미혼모의 양육스트레스에 관한 조사연구 현황을 분석하고 관련 개념을 탐구하고자 시행되었다. 4개 데이터베이스에서 지난 11년간 시행된 연구 14편이 선정되었다. 문헌은 연구 현황, 질평가, 주요 개념, 도구 및 주요 결과 등을 기준으로 분석되었다. 양육스트레스 관련 개념은 개인(인지, 정서 및행동) 요인과 사회/환경적 요인으로 분류하였다. 자아존중감, 양육효능감, 건강지각(인지), 우울, 애착안정성(정서), 양육 행동(행동), 그리고 사회적 지지와 부모, 아이 아버지와 타인의 지지(사회/환경적 요인)가양육스트레스 관련 요인으로 확인되었다. 신체적, 정서적 건강 문제를 확인하고, 국내 상황에서 사용할 수있는 신뢰할 만한 측정 도구 개발을 위한 연구가 필요하다. Background: The purpose of this study was to analyze current research trends on parenting stress of unmarried mothers in Korea and explore the related concepts. Methods: For searching the literature, KMbase, Korea Med, RISS, NDSL was used. Fourteen studies from 2009 to 2019 were selected, and National Institute of Health (NIH) Study Quality Assessment Tool (SQAT) was applied. Results: Among the 14 studies, most frequently used study design was correlational study (64.3%), and majority of the study (78.6%) was conducted in the field of social welfare. Only one study was found in the nursing journal. Related concepts can be categorized as individual (cognitive, emotional, and behavioral) factors, and social/environmental factors. Among these, self-esteem, parenting self-efficacy, and health perception in cognitive concept domain, depression in emotional concept domain, parenting behavior in behavioral domain, and lastly, social and interpersonal support were studied as related factors with parenting stress. Overall parenting stress level was higher than moderate, and it was positively related to depression, and negatively related to health perception and social support. Various study tools were used even the original foreign tool was the same, thereby comparisons among studies were difficult. Conclusions: Future studies are suggested to explore unmarried mother’s physical health problems as well as emotional problems, and to develop reliable measurement tools which can be used in Korean situation. Also, various nursing intervention programs for health promotion and child rearing competence for unmarried mothers should be developed. KCI Citation Count: 7